2003
DOI: 10.1053/rmed.2002.1420
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis in allergic rhinitis and asthma: methacholine dose–response slope allows a good differentiation between mild asthma and rhinitis

Abstract: Asthma and rhinitis frequently coexist in allergic patients, but nasal symptoms may predominate, leading to asthma underdiagnosis and undertreatment. Discriminant analysis obtains the best differentiation between groups using one or one set of variables. Our aim was to identify the laboratory test [allergen exposure, total and specific serum IgE, lung function, blood eosinophils and, bronchial response and sensitivity to methacholine (Mth) and allergen] or combination of them that allowed the best differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Wittig et al [23] reported that overlaps of serum IgE with normal values (of healthy volunteers) are the largest for patients of urticaria, eczema, and AR, and the least for patients with allergic asthma. A number of workers have also observed a significant difference between the IgE levels of asthmatics and AR patients in different populations [23][24][25][26]. However, the severity of AR was not taken into account in the present study and it is possible that the marked difference observed between IgE levels in asthma and rhinitis patients could be due to the fact that most of the patients of AR might be having mild to moderate rhinitis.…”
Section: Discussionmentioning
confidence: 62%
“…Wittig et al [23] reported that overlaps of serum IgE with normal values (of healthy volunteers) are the largest for patients of urticaria, eczema, and AR, and the least for patients with allergic asthma. A number of workers have also observed a significant difference between the IgE levels of asthmatics and AR patients in different populations [23][24][25][26]. However, the severity of AR was not taken into account in the present study and it is possible that the marked difference observed between IgE levels in asthma and rhinitis patients could be due to the fact that most of the patients of AR might be having mild to moderate rhinitis.…”
Section: Discussionmentioning
confidence: 62%
“…It is possible that some of the patients had coexistent asthma and rhinitis, but with nasal symptoms predominating, leading to an underdiagnosis and undertreatment of asthma 21 . Underdiagnosis by the GP has been reported in only 21% of cases, but poor perception of dyspnoea by the patient can cause up to a 66% underpresentation of respiratory symptoms 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Discriminant analysis in allergic rhinitis and asthma can be obtained from the methacholine dose-response (1931).…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%